Column: Black woman health: By the way, what about the Declaration on the Protection of Women and Children in Emergency and Armed Conflict? - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Nursing Diagnosis: Deficit of Justice for a mother (Edna Ezequiel, photo) whose adolescent daughter (Alana) and brother (Hélio Ezequiel) were killed in an urban armed conflict in Rio de Janeiro. Nursing Intervention: To implement the Declaration on the Protection of Women and Children in Emergency and Armed Conflict Proclaimed by General Assembly resolution 3318(XXIX) of 14 December 1974